Incorporation of FcRn‐mediated disposition model to describe the population pharmacokinetics of therapeutic monoclonal IgG antibody in clinical patients. (March 2016) - Ng, Chee M.
Abstract: Purpose . The two‐compartment linear model used to describe the population pharmacokinetics (PK) of many therapeutic monoclonal antibodies (TMAbs) offered little biological insight to antibody disposition in humans. The purpose of this study is to develop a semi‐mechanistic FcRn‐mediated IgG disposition model to describe the population PK of TMAbs in clinical patients. Methods . A standard two‐compartment linear PK model from a previously published population PK model of pertuzumab was used to simulate intensive PK data of 100 subjects for model development. Two different semi‐mechanistic FcRn‐mediated IgG disposition models were developed and First Order Conditional Estimation (FOCE) with the interaction method in NONMEM was used to obtain the final model estimates. The performances of these models were then compared with the two‐compartment linear PK model used to simulate the data for model development. Results . A semi‐mechanistic FcRn‐mediated IgG disposition model consisting of a peripheral tissue compartment and FcRn‐containing endosomes in the central compartment best describes the simulated pertuzumab population PK data. This developed semi‐mechanistic population PK model had the same number of model parameters, produced very similar concentration–time profiles but provided additional biological insight to the FcRn‐mediated IgG disposition in human subjects compared with the standard linear two‐compartment linear PK model. Conclusion . This first reported semi‐mechanistic model may serve as an important model framework for developing future population PK models of TMAbs in clinical patients. Copyright © 2015 John Wiley & Sons, Ltd.